Ranking, risk-taking and effort: an analysis of the ECB's foreign reserves management - Antonio Scalia; Benjamin Sahel (European Central Bank (ECB), 2011)
The investment of the ECB reserves in US dollars and yen, delegated to a network of portfolio managers in the Eurosystem's national central banks, involves a periodic assessment of performance against a common benchmark, controlled by the ECB and subject to revision on a monthly basis. Monetary reward for the best performers is almost entirely absent, and compensation comes mainly as reputational credit following the transmission of the annual report to the Governing Council. Employing a new data set on individual portfolio variables during 2002-2009, we study this peculiar tournament and show the existence of risk-shifting behaviour by reserve managers related to their year-to-date ranking: interim losers increase relative risk in the second half of the year, in the same way as mutual fund managers. In the dollar case, risk-shifting is asymmetric: the adjustment to ranking is generally reduced or entirely offset if reserve managers have achieved a positive interim performance against the benchmark. Yen reserve managers that rank low show a tendency to increase effort, as proxied by portfolio turnover. We also find that reserve managers who ranked low in the previous year tend to reduce risk significantly. Our evidence is consistent with a reserve managers' anecdote, according to which they obtain a concave reputational reward within their national central banks, which induces risk aversion and explains the observed low usage of the risk budget. Since reserve managers should have a comparative advantage over the tactical benchmark within a monthly horizon, possible enhancements to the design of the tournament are discussed. These might involve an increased reward for effort and performance by means of a convex scoring system linked to monthly, rather than annual, performance.
Keywords: G11; E58; D81; 330; Delegated portfolio management; effort; Foreign reserves; incentives; tournament